Islands of heat and the importance of urban tree-planting in Paço de Lumiar municipality, MA, Brazil (Research, Society and Development, 2022)
The Municipality of Paço do Lumiar, MA, is located On São Luis Island. The main natural vegetation types are Amazonian rainforest and (the largest category). However, its green area has been drastically reduced over the last 20 years as a result of the real estate development. This study aimed to characterize the remianing forested areas and identify the heat islands in the urban area of Paço do Lumiar municipality. Accordingly, primary and secondary data were collected on vegetation cover within the municipality and its heat islands. Urban afforestation is often inadequate, failing to meet basic landscaping and urbanization requirements, with many planted species unsuitable for these purposes. Among such species, the most common are Ficus benjamina L. (fig) and Terminalia catappa L. (beach almond). Accordingly secondary lowest, vegetation indices mostly occurred in the southwest area of the municipality, the areas of densest human-occupation, such as the Maiobão borough, occur. On the dates analyzed, surface temperatures reached 37°C ,while the lowest values were recorded in areas with greatest percntages of water and natural vegetation cover. This indicates that areas with higher water availability and vegetation cover may help mitigate the effects of termal anomalies, such as heat islands, which strongly influence the climatic comfort of urban human populations. For these reasons, it is necessary to create an Afforestation Manual or Municipal Afforestation Plan for Paço do Lumiar Municipality to alleviate the problem of heat islands in the most densely populated neighborhoods.